Analysis of hair remains from a hunter-gatherer grave from Patagonia: Taxonomic identification and archaeological implications - Prates, Luciano Raúl (2016)
The results of the analysis of hair remains froma hunter-gatherer grave fromnorthern Patagonia are presented in this paper. One of the samples analyzed consisted in hair that remained attached to the hide used to manufacture a small pouch left in the burial pit as a funerary offering. The second samplewas taken fromthe inside of the same pouch. The hair taxonomic determination was performed by considering cross-sections of the hairs, the patterns of the medulla, and the shape and disposition of the cuticle scales by microscopic observation ofmolds of the hair surfaces. Samples were identified as Lagidium viscacia and Homo sapiens, respectively. These results provide the first evidence of both the exploitation ofsmall mammal (Lagidium) hide and the offering of human hair in a grave, among Patagonian hunter-gatherers.